Identification, molecular characterization and differential expression studies of genes activated during Coffea arabica L. - Hemileia vastatrix interactions Berk. & Broome - Barka, Geleta Dugassa (2017)
Coffee is one of the most valued cash crops making the economies of many developing countries and sustaining the livelihoods of millions around the world. Despite many decades of breeding efforts with great achievements in incorporating resistance components into elite cultivars, coffee leaf rust (caused by Hemileia vastatrix) is increasingly damaging coffee production. Understanding the molecular mechanisms of rust resistance is believed to play a vital part in enhancing resistant cultivar development. The objective of the present work is to understand the expression patterns of resistance genes activated following pathogen inoculation and characterize some major resistance genes. Suppression subtractive hybridization (SSH) was used to identify genes differentially over expressed and repressed at 12 and 24 hours after pathogen inoculation during incompatible and compatible interactions between C. arabica and H. vastatrix. From 433 clones of expressed sequence tags (ESTs) sequenced, 352 were annotated and categorized of which the proportion of genes expressed during compatible interaction were relatively smaller. RT-qPCR analysis of seven resistance-signaling genes showed similar expression patterns for most of the genes in both interactions, indicating these genes are involved in basal (non-specific) defense during which immune reactions are similar. In another experiment, resistance gene analogs (RGAs) conferring coffee rust resistance were identified from a BAC library, sequenced and characterized. Five RGAs were annotated and mapped to chromosome 0 of C. canephora. Four of the RGAs are actively expressed during C. arabica-H. vastatrix incompatible interaction. The result obtained in this work suggests that one of the RGAs sequenced (gene 11) is a new S H gene (S H 10) not yet identified biologically. We also report an S H gene (S H 10) in differential host clone 644/18 H. Kawisari for the first time. Moreover, comparative analysis of two RGAs belonging to the CC-NBS-LRR gene family showed intense diversifying selection due to nonsynonymous substitution and genetic recombination. Phylogenetic analysis of orthologous genes showed high interaspecies variability among the two genes in related species than in coffee. Overall, differential gene expression analysis provided a compiled expression profile of genes upregulated and downregulated at 12 and 24 h. a. i. during incompatible and compatible interactions. Likewise, the NBS- LRR genes sequenced in this work are the largest and most complete gene reported in Arabica coffee to date, which makes the work extremely important for molecular breeding of coffee rust resistance.